Model to increase the use of production capacity using Lean tools in the paint subsector - Allison Lizeth, Garcia Contreras (2022)
Currently, the contribution to the PBI of the construction sector has increased, which generates a greater demand for its products. Also, the production of paints fails to meet the demand generated, so the problem to be addressed in this article is the use of production capacity in a manufacturer of industrial paints with an annual turnover of approximately 80 million soles, which currently uses an average of 53.29% of its installed capacity, below the 69.7% average of the sector, generating large losses of money for the company. The case study was carried out so that it can be replicated with other companies with a similar context and generate added value to the sector, therefore an improvement model is proposed by applying the tools and methodology of Aggregate Planning, Autonomous TPM and SRM through the integrated application of the above mentioned providing an efficient production planning, an improved maintenance plan and the approval of suppliers. Validation of the tools was performed with case studies that presented similar problems. The proposed model implements and integrates the main techniques, managing to increase mill availability to 93%, reduce reprocesses and the percentage of error in the demand forecast by up to 1% and eliminate the stock-out of raw material, thereby increasing the use of production capacity. Finally, an increase of 16% is obtained for the use of production capacity, with an NPV of $68,732 and IRR of 45.54%, which indicate that the project is profitable and optimal for the company.